Crosslinking of Chitosan with a Trifunctional Crosslinker and the Adsorption of Acid Dyes and Metal Ions onto the Resulting Polymer - Yoshiaki Shimizu; Yoshihiro Saito; Takeo Nakamura (Adsorption Science & Technology)
Novel chitosan-based adsorbent materials were synthesized using a trifunctional reagent as a crosslinker and the adsorption capability of the resulting polymers towards two acid dyes and several metal ions was evaluated. The crosslinked chitosan with the lowest degree of substitution showed a very high adsorption capability towards CI Acid Orange 7. Decreasing the degree of substitution and the pH of the dye solution led to an increase in the adsorption capability. The crosslinked chitosan with the lowest degree of substitution exhibited quite remarkable adsorption powers towards the Cu 2+ ion. Such adsorption towards divalent metal ions decreased in the following sequence: Cu 2+ » Ni 2+ > Cd 2+ , Pb 2+ , Ca 2+ .